Dengue virus serotype 2 infection alters midgut and carcass gene expression in the Asian tiger mosquito, Aedes albopictus - Tsujimoto, Hitoshi (PLoS One, 2017)
BACKGROUND: The Asian tiger mosquito, Aedes albopictus is currently an important vector for dengue, chikungunya and Zika virus, and its role in transmission of arthropod-borne viruses (arboviruses) may increase in the future due to its ability to colonize temperate regions. In contrast to Aedes aegypti, the dominant vector of dengue, chikungunya and Zika virus, genetic responses of Ae. albopictus upon infection with an arbovirus are not well characterized. Here we present a study of the changes in transcript expression in Ae. albopictus exposed to dengue virus serotype 2 via feeding on an artificial bloodmeal. METHODOLOGY/PRINCIPAL FINDINGS: We isolated midguts and midgut-free carcasses of Ae. albopictus fed on bloodmeals containing dengue virus as well as controls fed on virus-free control meals at day 1 and day 5 post-feeding. We confirmed infection of midguts from mosquitoes sampled on day 5 post-feeding via RT-PCR. RNAseq analysis revealed dynamic modulation of the expression of several putative immunity and dengue virus-responsive genes, some of whose expression was verified by qRT-PCR. For example, a serine protease gene was up-regulated in the midgut at 1 day post infection, which may potentially enhance mosquito susceptibility to dengue infection, while 14 leucine-rich repeat genes, previously shown to be involved in mosquito antiviral defenses, were down-regulated in the carcass at 5 days post infection. The number of significantly modulated genes decreased over time in midguts and increased in carcasses. CONCLUSION/SIGNIFICANCE: Dengue virus exposure results in the modulation of genes in a time- and site-specific manner. Previous literature on the interaction between mosquitoes and mosquito-borne pathogens suggests that most of the changes that occurred in Ae. albopictus exposed to DENV would favor virus infection. Many genes identified in this study warrant further characterization to understand their role in viral manipulation of and antiviral response of Ae. albopictus.